THE EFFECT OF WORD OF MOUTH (WOM) AND BRAND IMAGE ON PURCHASE DECISIONS (SURVEY ON CUSTOMER OF ONLINE TRANSPORTASION GOJEK SUKABUMI) - Ryan Kurniawan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The reason of this research was to determine the effect of word of mouth and brand image on the purchase decision of GOJEK. This investigate could be a quantitative approach inquire about. The population in this study is the people of Sukabumi City who have used GOJEK. The sampling technique uses accidental sampling method with a sample of 100 people. Data processing was carried out using Descriptive Analysis and Multiple Linear Regression Analysis using SPSS25. The results of this study indicate that the variables of word of mouth and brand image have a significant effect on the purchase decision of GOJEK online transportation services, simultaneously and partially.